Factors Affecting Students’ Continuous Intention to Use Online Art Education Software in Chengdu, China - Chen, Fangrui; Phongsatha, Satha (Scholar: Human Sciences, 2023)
Purpose: This study aims to explore the analysis of factors influencing the continuous use of online art education software by private art education institutions in Chengdu, Sichuan Province, China. The conceptual framework is based on TAM, UTAUT, and IS success model, indicating the relationship between self-efficacy, perceived ease of use, perceived usefulness, attitude, satisfaction, information quality, and continuous intention to use. Research design, data, and methodology: The researchers used quantitative methods (n=500) to distribute questionnaires to students at three private fine arts institutions. Confirmatory factor analysis (CFA) and a structural equation model (SEM) were used for data analysis, including model fitting, reliability, and validity of the structure. Results: The results indicate that satisfaction and attitude are significant factors affecting the continuous use intention of online art education software. Perceived ease of use has the most significant effect on perceived usefulness. Among them, the perceived usefulness and perceived ease of use significantly affect the attitude. Furthermore, information quality significantly impacts students’ satisfaction with using online art education software. However, self-efficacy has no significant effect on perceived ease of use. Conclusions: Therefore, this study suggests that educators should create a more suitable learning platform for combining technology and art in the course design and teaching of online art education software.